Design and analysis of a shape-transformable polyhedral mechanism with transformation between a truncated tetrahedron and a tetrahedron. (November 2020) - Kong, Fanchen; Liu, Jingfang; Ding, Huafeng
The aim of this study is to present a novel shape-transformable polyhedral mechanism namely, the TrT–T mechanism, which can transform between a truncated tetrahedron and a common tetrahedron. The conceptual model of the TrT–T mechanism is proposed and described. For one-degree-of-freedom objective, a hexagonal planar linkage is chosen as a hexagonal interlinked unit to develop a solid model and fabricate a prototype. Mobility analysis is carried out based on screw theory. The inverse and forward kinematics are investigated, and the singularity is analyzed. The trajectories and velocities of the hinge points are described and explored. The prototype and simulation results demonstrate the feasibility of the TrT–T mechanism for shape transformation and validate the correctness of the mobility analysis. As a novel polyhedral linkage, the TrT–T mechanism can be potentially applied to modules with shape-transformation ability for constructing reconfigurable and modular robots.